Wearing cultural styles in Japan : concepts of tradition and modernity in practice - Thompson, Christopher, 1962-; Traphagan, John W. (Albany : State University of New York Press, 2006)
Annotation This groundbreaking collection examines the regional dynamics of state societies, looking at how people use the concepts of urban and rural, traditional and modern, and industrial and agricultural to define their existence and the experience of living in.
The practice of tradition and modernity in contemporary Japan / John W. Traphagan and Christopher S. Thompson -- The social impact of rural-urban shift : some Akita examples / John A. Mock -- Rice revolutions and farm families in Tōhoku : why is farming culturally central and economically marginal? / William W. Kelly -- Young women making lives in northeast Japan / Nancy R. Rosenberger -- Negotiating internationalization in Kitasawa / Tomoko Watanabe Traphagan -- Preserving the Ochiai deer dance : tradition and continuity in a Tōhoku hamlet / Christopher S. Thompson -- Heartbreak's destination : Tōhoku in the poetic discourse of Enka / Debra J. Occhi -- Tradition and modernity merged in Tsugaru Nuri lacquerware : perspectives of preservation and promotion, production and consumption / Anthony S. Rausch -- Epilogue : Tōhoku : a place / L. Keith Brown.
Includes bibliographical references and indexes.
Print version record.
eBooks on EBSCOhost
Keywords: Japan -- Social conditions -- 1945-; Japan -- Civilization -- 1945-; Social change -- Japan; Culture and globalization -- Japan; Japon -- Conditions sociales -- 1945-; Japon -- Civilisation -- 1945-; Culture et mondialisation -- Japon; HISTORY; Civilization; Culture and globalization; Social change; Social conditions; Japan; Since 1945